2008
DOI: 10.3113/fai.2008.0072
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Frontal Plane Position on First Ray Motion: Forefoot Locking Mechanism

Abstract: This study demonstrates that the frontal plane position of the first ray affects the sagittal plane motion. An everted position has the least mobility, and we hypothesize that this represents a closed-packed or locked position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 12 publications
0
11
2
Order By: Relevance
“…Previous research found a more inverted medial forefoot during the stance phase of gait in subjects with CAI, which reflects a mechanically less stable position [23]. This mechanism was, however, not observed during our landing tasks in subjects with CAI.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous research found a more inverted medial forefoot during the stance phase of gait in subjects with CAI, which reflects a mechanically less stable position [23]. This mechanism was, however, not observed during our landing tasks in subjects with CAI.…”
Section: Discussioncontrasting
confidence: 58%
“…This may explain why the two groups only displayed difference in the AbH size in a relatively small sample size of the current study. Furthermore, the action of AbH to flex the first ray and invert the calcaneus could aid in forefoot locking and midtarsal joint locking mechanisms . This muscle also contributes to the stabilization and supination of the midtarsal joint during propulsion .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the change in the morphology of the 1MT might have occurred developmentally due to an age-associated decrease in force-generating capacity of the foot muscles and, hence, altered biomechanics of the foot. In particular, degeneration of peroneus longus could be a primary factor for the twisted 1MT, because the function of this muscle is to bring the proximal metatarsals into a closely packed position by everting the 1MT to stabilize the forefoot [ 25 , 26 ]. Therefore, decreased pull of peroneus longus might alter the twisting moment generated in the 1MT, leading to adaptive change in the morphology of the 1MT.…”
Section: Discussionmentioning
confidence: 99%